Development and mechanical performance evaluation of a GFRP-reinforced concrete boat-approach slab. (December 2022) - Manalo, Allan; Alajarmeh, Omar; Yang, Xian; Ferdous, Wahid; Ebrahimzadeh, Shahrad; Benmokrane, Brahim; Sorbello, Charles-Dean; Weerakoon, Senarath; Lutze, Darren
Abstract: The use of glass fiber-reinforced polymer (GFRP) composite bars as internal reinforcement in concrete structures exposed to marine and aggressive environments has gained popularity in recent years. The fact that designers and workers are unfamiliar with the design and handling of GFRP bars contributes to GFRP bars being used less often than traditional steel reinforcement bars. This case study presents the construction and loading test for GFRP-reinforced concrete boat-approach slab. Two types of reinforcement mesh stemmed from a similar design requirement were implemented: 16 mm diameter bars spaced 150 mm apart in both directions and 24 mm diameter bars spaced 300 mm apart in both directions to evaluate the fabrication and installation efficiency with GFRP bars. Loading tests and monitoring were employed to evaluate the field performance of the GFRP-reinforced slab. The results show that a slab reinforced with 16 mm diameter GFRP bars can be durable and reliable, and can increase worker productivity during handing and installation. Moreover, considering the appropriate subgrade modulus for the supporting ground in the design and analysis can lead to a more cost-effective design of GFRP-reinforced concrete approach slabs. Lastly, this case study demonstrates the durability and resilience of GFRP-reinforced concrete as boating infrastructure.